PENANGANAN DISMENOREA PADA REMAJA PUTRI - Anthoneta J. Hitipeuw; Ismiyanti Achmad (Jurnal Kebidanan, 2022)
One of the most common complaints felt by young women during menstruation is menstrual pain or dysmenorrhea, and has different degrees of pain in each person ranging from mild to severe. Dysmenorrhea is pain accompanied by pain and is a common problem experienced by women of different age levels, not a few women experience the discomfort of having menstruation. Dysmenorrhoea is a medical condition that occurs during menstruation or menstruation characterized by pain or pain in the abdominal and pelvic areas that can interfere with daily activities and require treatment. This situation is also accompanied by nausea, vomiting, and fainting. These complications can actually be prevented and treated but there is no awareness of adolescents seeking health services. In this case, in case of abdominal pain, the client Ms. A immediately buys an over-the-counter analgesic drug at the drugstore/dispensary. Treatment efforts are to encourage the client to give warm compresses, the curled up position like a fetus is the best sleeping position to relieve pain, distracting techniques, doing light exercise, Support from parents and health workers (midwives) is continuously needed to be able to overcome the problems experienced by the client.